Iron Oxide Nanoparticles Induced Histological Alteration and Fetal Skeletal Abnormalities in the Embryo of Albino Rats (Medico Legal Update, 2020)
The study was carried out to investigate the effect of iron oxide nanoparticle(NP) on the brain, liver, spleen and vertebral colum in the embryo of albino rats at the age of 19 day of pregnancy . The study included twenty (20) embryos divided into two groups ,treated and control group . The results of the histological study reveled the existence of histological alteration in the brain, liver, spleen and vertebral colum of treated groups compared with controls .